2022
DOI: 10.7759/cureus.22670
|View full text |Cite
|
Sign up to set email alerts
|

Male Breast Cancer: The Three Decades' Experience of a Tertiary Care Hospital in a Lower-Middle Income Country

Abstract: IntroductionMale breast cancer is uncommon and managed on the guidelines of female breast cancer due to tumor rarity. We sought to identify the incidence, clinicopathological features, and survival of all male breast cancer patients managed in our hospital. MethodsA retrospective cross-sectional study was conducted at Aga Khan University Hospital (AKUH), Karachi, Pakistan, from January 1986 to December 2018. Demographic data, treatment records, and follow-up data of all male breast cancer patients who were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…In total, adjuvant ET was indicated in 90% of hormone receptor-positive patients (N=201). This number is very high, contrary to some researchers who report that only 57.9% [4,20], 67.3% [21], and 76.8% [6] of men with hormone receptor-positive MBC were treated with ET. We assumed that, in addition to the region, this also depends on organization and/or quality of care.…”
Section: Overall Outcomescontrasting
confidence: 63%
“…In total, adjuvant ET was indicated in 90% of hormone receptor-positive patients (N=201). This number is very high, contrary to some researchers who report that only 57.9% [4,20], 67.3% [21], and 76.8% [6] of men with hormone receptor-positive MBC were treated with ET. We assumed that, in addition to the region, this also depends on organization and/or quality of care.…”
Section: Overall Outcomescontrasting
confidence: 63%
“…Adjuvant ET was indicated for 92% of hormone receptor-positive M0 patients. This number is very high compared with prior studies, in which ET was indicated for 57.9%, 4 , 24 67.3%, 25 and 76.8% 6 of men with hormone receptor-positive MBC. Only 5% of patients discontinued ET due to their performance status, treatment intolerance, or treatment refusal.…”
Section: Discussionmentioning
confidence: 53%
“…Invasive carcinoma of no special type (NST) is the most common MBC [11]. Histologic types of ductal origin occur relatively more frequently in men than in women, reflecting the absence of lobular structures in the normal male breast; those of lobular origin are very uncommon in men [10,12].…”
Section: Introductionmentioning
confidence: 99%